Impact of Subinhibitory Concentrations of Metronidazole on Morphology, Motility, Biofilm Formation and Colonization of Clostridioides difficile - Tri-; Marie-Françoise; Sandra Hoÿs; Claire Janoir; Séverine Péchiné (MDPI AG, 2022)
Clostridioides difficile infection (CDI) is the primary cause of health-care-associated infectious diarrhea. Treatment requires mostly specific antibiotics such as metronidazole (MTZ), vancomycin or fidaxomicin. However, approximately 20% of treated patients experience recurrences. Treatment with MTZ is complicated by reduced susceptibility to this molecule, which could result in high failure and recurrence rates. However, the mechanism remains unclear. In this study, we investigated the impact of subinhibitory concentrations of MTZ on morphology, motility, biofilm formation, bacterial adherence to the intestinal Caco-2/TC7 differentiated monolayers, and colonization in monoxenic and conventional mouse models of two C. difficile strains (VPI 10463 and CD17-146), showing different susceptibility profiles to MTZ. Our results revealed that in addition to the inhibition of motility and the downregulation of flagellar genes for both strains, sub-inhibitory concentrations of MTZ induced various in vitro phenotypes for the strain CD17-146 exhibiting a reduced susceptibility to this antibiotic: elongated morphology, enhanced biofilm production and increased adherence to Caco-2/TC7 cells. Weak doses of MTZ induced higher level of colonization in the conventional mouse model and a trend to thicker 3-D structures entrapping bacteria in monoxenic mouse model. Thus, sub-inhibitory concentrations of MTZ can have a wide range of physiological effects on bacteria, which may contribute to their persistence after treatment.